2021
DOI: 10.4103/mjdrdypu.mjdrdypu_242_20
|View full text |Cite
|
Sign up to set email alerts
|

Use of Internet for Practice of Self-Medication

Abstract: Background: Internet has become the major source of health-related information, leading to a growing trend toward unsupervised self-medication using internet. This survey was conducted to assess the extent of internet use to obtain health information/self-medication, their perception regarding side effects of drug used, types/quality of information, and which site was commonly surfed for information. Materials and Methods: A web-based tool (Google Forms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 11 publications
2
11
0
1
Order By: Relevance
“…The most potential sources of information of drug for SM had been found as pharmacists, previous prescriptions, friends and family. The same trends have also been documented by earlier works too both from the urban and rural areas in India [1,3,4,10,14,28,32]. But the present study has found the prominent role of the internet, social media and peers in promoting the habit of SM among the young and educated females in Chandigarh.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The most potential sources of information of drug for SM had been found as pharmacists, previous prescriptions, friends and family. The same trends have also been documented by earlier works too both from the urban and rural areas in India [1,3,4,10,14,28,32]. But the present study has found the prominent role of the internet, social media and peers in promoting the habit of SM among the young and educated females in Chandigarh.…”
Section: Discussionsupporting
confidence: 90%
“…In the current study age, work-profile, loneliness, lack of social security, availability of information and resources of drugs were found to be significantly related to the rising trends of SM among young females in the city. Similar relationships in the younger populations were observed by other workers also [4,19,22,27,29].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Although self-medication might save time and money, it also has hazards associated, such as antibiotic resistance or improper management leading to complications [1]. One of the studies showed that almost 60% of people who self-medicate use the internet as a source, and the majority (54.47%) took medications without consulting doctors [2]. The prevalence of self-medication was 69.0% among nonmedical students, whereas headache was the predominant ailment for which the medications were used.…”
Section: Introductionmentioning
confidence: 99%